Quality of Life, Psychological Functioning, and Treatment Satisfaction of Men Who Have Undergone Penile Prosthesis Surgery Following Robot-Assisted Radical Prostatectomy. Issue 12 (27th October 2017) - Pillay, Brindha; Moon, Daniel; Love, Christopher; Meyer, Denny; Ferguson, Emma; Crowe, Helen; Howard, Nicholas; Mann, Sarah; Wootten, Addie
Abstract: Background: Penile prosthesis surgery is last-line treatment to regaining erectile function after radical prostatectomy (RP) for localized prostate cancer. Aims: To assess quality of life, psychological functioning, and treatment satisfaction of men who underwent penile implantation after RP; the psychosocial correlates of treatment satisfaction and sexual function after surgery; and the relation between patients' and partners' ratings of treatment satisfaction. Methods: 98 consecutive patients who underwent penile implantation after RP from 2010 and 2015 and their partners were invited to complete a series of measures at a single time point. Of these, 71 patients and 43 partners completed measures assessing sexual function, psychological functioning, and treatment satisfaction. Proportions of patients who demonstrated good sexual function and satisfaction with treatment and clinical levels of anxiety and depression were calculated. Hierarchical regression analyses were conducted to determine psychosocial factors associated with patient treatment satisfaction and sexual function and patient-partner differences in treatment satisfaction. Outcomes: Patients completed the Expanded Prostate Cancer Index Composite Short Form (EPIC-26), Erectile Dysfunction Inventory of Treatment Satisfaction (EDITS), Prostate Cancer-Related Quality of Life Scale, Self-Esteem and Relationship Questionnaire (SEAR), Generalized Anxiety Disorder–7 (GAD-7), and Patient Health Questionnaire–9 (PHQ-9). Partners completed the GAD-7, PHQ-9, EDITS (partner version), and SEAR. Results: 94% of men reported satisfaction with treatment (EDITS score > 50). 77% of men reported good sexual function (EPIC-26 score > 60). Lower depression scores were associated with higher sexual confidence and sexual intimacy, and these were correlated with better treatment satisfaction and sexual function. Patients experienced higher sexual relationship satisfaction (median score = 90.6) than their partners (median score = 81.2), but there was no difference in treatment satisfaction between groups. Higher patient treatment satisfaction was more likely to be reported for couples whose depression scores were more similar. Clinical Implications: It is important to provide preoperative penile implant counseling and encourage patients to seek postoperative counseling if needed. Strengths and Limitations: This is one of the first Australian-based studies comprehensively assessing treatment satisfaction and psychosocial health of men after penile prosthesis surgery after RP. This was a retrospective cross-sectional study, so there is a possibility of recall bias, and causal associations could not be determined. Conclusion: Men in this Australian series who underwent penile prosthesis surgery after RP generally reported good sexual function and treatment satisfaction. Nevertheless, patient and partner mental health influenced their reported experience of the treatment.